Menganalisis Biaya Produksi Full Costing Dan Variable Cost Terhadap Metode Biaya Pada Hasil Penjualan Pada Toko Kopi Miyami di Cikarang - Purwanti Purwanti; Alfia Yunita Indriyani; Cania Masrifa Hadis; Suci Rahmanda Putri; Salman Al Faridzi; Dimas Pratama Yuda; Hafidz Fachri Akbar; Rensisca Vivi Andari; Amelia Dwi Ananda Kontesa; Salsabila Putri Luthfiasari; Rendy Juniardi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This research aims to analyze the influence of full costing and variable costing production methods on the sales results of coffee products at the Micro, Small, and Medium Enterprises (MSMEs) Kopi Miyami in Cikarang. The background of this research is based on the increase in domestic coffee consumption and the trend of the 'ngopi' lifestyle which makes coffee shops an integral part of urban social activities. This study adopts a qualitative approach with purposive sampling techniques, resulting in 80 monthly observation data. The research results indicate that both production cost methods, such as full costing and variable costing, significantly influence sales results. Regression coefficients show that the variable costing method has a more dominant influence on increasing sales results compared to the full costing method. Based on these findings, this research suggests that MSMEs in the food and beverage sector, particularly coffee shops, considering the use of variable costing methods in calculating their production costs. This aims to support efficiency, competitive pricing, and optimal sales improvement.